Modulation of the endogenous Annexin A1 in a cigarette smoke cessation model: Potential therapeutic target in reversing the damage caused by smoking? - Lebron, Isabella de Souza Lima (2019)
Background: Smoking cessation may help in the reversal of inflammation and damage caused by smoking. The endogenous annexin A1 (AnxA1) protein has anti-inflammatory effects which instigates the understanding of its role in the attenuation of inflammatory processes caused by smoking. Material and methods: Wistar rats were exposed to cigarette smoke for 8 weeks. After the exposure period, one of the groups remained other 8 weeks in the absence of smoke. Animals not exposed to smoke were used as control. Blood, trachea and lungs were obtained for histopathological, immunohistochemical and biochemical analyses. Results: Loss of cilia of the tracheal lining epithelium was found by smoke exposure, but smoking cessation led to recovery of the tracheal epithelium. Similarly, chronically exposed-to-smoke animals showed increased lymphocytes and macrophages in bronchoalveolar lavage and higher levels of glucose and gamma-GT in their blood. Reduction of lymphocytes, glucose and gamma-GT occurred after smoking cessation. In addition, IL-1β, IL-6, IL-10, TNF-α and MCP-1 levels were elevated by smoke exposure. Smoking cessation significantly reduced the levels of IL-1β, IL-6 and MCP-1 but increased the IL-10 concentration. Numerous mast cells and macrophages were observed in the lung of chronically exposed-to-smoke animals with reduction by smoking cigarette abstinence. AnxA1 increased expression and concomitant NF-κB reduction were found in the smoking cessation group. Conclusion: Our results showed that cigarette abstinence promoted partial recovery of the inflammatory process. The attenuation of the inflammatory profile may be associated with the overexpression of AnxA1 protein.